Hype how scammers, grifters, and con artists are taking over the internet--and why we're following - Bluestone, Gabrielle (HarperCollins Publishers, 2021)
The former "Vice" journalist and producer of the Netflix documentary, "Fyre," presents a revelatory examination of the con-artists, grifters, and scammers of the digital age that outlines recommendations for protecting consumers